ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Monic Lisiana, Kezia Xenna; Widyarti, Endang Tri (Diponegoro Journal of Management, 2021)
Capital structure is an important factor in a company because it is directly related to the continuity of the company's life. There are several factors that can affect the capital structure. This study aims to examine the influence of several factors, namely: liquidity, business risk, asset structure, profitability, and company size, on capital structure, which will be proxied by the Long-term Debt to Equity Ratio (LTDER), which is carried out in manufacturing companies listed on the Indonesia Stock Exchange during the period 2014 to 2018.Â Â This study uses trade-off theory and pecking-order theory as a reference basis. The sample of this research is 70 companies which is using purposive sampling method as the basis for sampling. The data collected through financial reports and Bloomberg. This research hypothesis testing using multiple linear regressions accompanied by conducting classic assumptions test on the data to be used. The analysis tool used in this study is by the SPSS 25 program.The findings of this study indicate that liquidity and profitability have a negative and significant effect on capital structure. The variables of asset structure and company size show a significant and positive effect. Meanwhile, the business risk variable does not significantly affect in this study.